Schedule reliability in liner shipping : current practice, causes and possible solutions - Wei, Xiaona. (2013)
Purpose- This report aims to study and analyze the current schedule reliability performance of major liner alliances (G6, New World Alliance and CMA CGM-MSC) in key east-west trade routes (Singapore-Rotterdam and Singapore-Los Angeles), and propose strategies from a supply chains’ perspective to improve liner schedule reliability or to minimize effects of schedule unreliability.